2000
DOI: 10.1677/joe.0.1650051
|View full text |Cite
|
Sign up to set email alerts
|

Localization of prostaglandin synthase type-1 (PGHS-1) mRNA and prostaglandin synthase type-2 (PGHS-2) mRNA in ovine myometrium and endometrium throughout gestation

Abstract: Increased prostaglandin production by tissues in the sheep uterus and placenta are thought to be important for the onset of parturition. In the sheep placenta, this is most likely due to increased expression of prostaglandin synthase type-2 (PGHS-2) rather than prostaglandin synthase type-1 (PGHS-1). However, there is no information concerning expression of PGHS isoenzymes in maternal uterine tissues during pregnancy. Therefore, the purpose of the present study was to examine the expression of PGHS-1 and PGHS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, we and others have demonstrated that IL-1β, TNFα and IL-6 can increase prostaglandin production by amnion, decidua and myometrium [11, 21, 22, 70, 73, 138140, 155, 175, 198, 199, 202, 294, 325]. PTGS2/COX2 is a rapidly inducible enzyme with reported increased expression in association with labor in myometrium [5, 6, 44, 54, 67, 115, 136, 233, 278, 284, 289, 306] and the uterine cervix [26, 67, 132, 186, 230, 297, 313, 330, 331]. Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we and others have demonstrated that IL-1β, TNFα and IL-6 can increase prostaglandin production by amnion, decidua and myometrium [11, 21, 22, 70, 73, 138140, 155, 175, 198, 199, 202, 294, 325]. PTGS2/COX2 is a rapidly inducible enzyme with reported increased expression in association with labor in myometrium [5, 6, 44, 54, 67, 115, 136, 233, 278, 284, 289, 306] and the uterine cervix [26, 67, 132, 186, 230, 297, 313, 330, 331]. Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%